THE STATE DETERMINES LEGAL SYSTEM WITH INTERNATIONAL HUMAN RIGHTS INSTRUMENTS - ARIEF FAHMI LUBIS (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
Human rights, which are protected can be in the form of individuals, groups or property. The state or state officials as part of the state have an international obligation to protect citizens and their property, where international human rights standards are established and developed in various international forums. The purpose of this study is to review the Conventions related to Human Rights which guarantee the right of everyone to be treated equally before the law regardless of race, color, origin and ethnicity, which also establishes the Committee on the Elimination of Racial Discrimination, which oversees its implementation. Qualitative research uses a descriptive approach to collect data systematically, factually, and quickly according to the description when the research is carried out. The results of this study indicate that the Human Rights Principles provide guidance for law enforcers in prosecuting criminals. These principles emphasize the importance of oversight (including clarity in the chain of command) of law enforcement agencies. These principles also explain in detail the guarantee of the fulfillment of the right to life.